Investigation of thermodynamic properties of 4-decyloxybiphenyl-4′-carboxylic acid liquid crystal and preparation of polymer dispersed liquid crystal composite - Ozturk, Emine; Ocak, Hale; Cakar, Fatih; Karanlik, Gurkan; Cankurtaran, Ozlem; Bilgin-Eran, Belkis (ELSEVIER, 2018)
In this study, firstly, retention behavior of solvents on the liquid crystalline material 4-decyloxybiphenyl-4'-carboxylic acid (DBCA) has been studied by inverse gas chromatography (IGC) technique. Liquid crystal (LC) selectivity was investigated using the acetate isomers by the IGC method at temperatures between 333.2 K and 543.2 K. Later on, the interactions of LC with n-octane, n-nonane, n-decane, undecane, dodecane, tridecane, npropyl benzene, isopropyl benzene, ethylbenzene, chlorobenzene and toluene between 518.2 K and 543.2 K were examined. LC-solvent interaction parameters for Flory-Huggins theory, chi(12)*, and equation of state theory, chi(12)*, effective exchange energy parameters, X-eff, the weight fraction activity coefficent, Omega(infinity)(1), the partial molar heat of mixing at infinite dilution of the solvent, Delta H-1(infinity), molar heat of vaporization of solvent, Delta H-v and the partial molar heat of sorption of the solvent, Delta H-1,H-s were obtained. Secondly, polymer dispersed liquid crystal (PDLC) composite film in composition 20/80 poly( methyl methacrylate) (PMMA):DBCA by weight was synthesized by solvent-induced phase separation method. The mesomorphic behavior of DBCA and PDLC composite has been investigated by differential scanning calorimetry (DSC) and optical polarizing microscopy (PM). (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Liquid crystal; Thermodynamic interaction parameters; Inverse gas chromatography; Poly(methyl methacrylate); Polymer dispersed liquid crystal composite; INVERSE GAS-CHROMATOGRAPHY; SURFACE; TRANSITIONS; PARAMETERS; PHASES; Chemistry; Physics